The task of the critic poetics, philosophy, and religion - Sussman, Henry 1947- (New York Fordham University Press, 2005)
The task of the critic : a game of registers -- Prolegomena to any present and future language poetry -- Walter, the critic -- Between the registers : The Arcades Project, the Talmud, and Glas -- Deterritorializing the text : flow theory and deconstruction -- Derrida as critic : a Joycean odyssey -- The fourth Abrahamic religion?
The task of the critic : a game of registers -- Prolegomena to any present and future language poetry -- Walter, the critic -- Between the registers : the Arcades Project, the Talmud, and Glas -- Deterritorializing the text : flow theory and deconstruction -- Derrida as critic : a Joycean odyssey -- The fourth Abrahamic religion?
Includes bibliographical references and index
Archivierung prüfen
Keywords: Criticism -- History -- 20th century; Criticism; Criticism (Philosophy)